"Break the Silence Bangladesh": Examining "everyday" experiences of sexual violence through online activism. (July 2020) - Chowdhury, Rashaam; Fileborn, Bianca
Abstract: In 2015, the Pahela Baishakh (Bengali New Year) celebrations in Bangladesh were marred by incidents of mass sexual assaults. This incident generated widespread public discussion, and many survivors took to the digital realm to disclose their own experiences. Break the Silence Bangladesh was a Facebook page established to provide a space for shared disclosure, support and consciousness-raising. In this paper, we analyse 61 submissions made to the page, which provide vital insights into experiences of sexual violence in Bangladesh outside of the dominant frame of domestic and intimate partner violence. Findings point to the diverse range of contexts in which sexual violence occurs, the roles of class and space in shaping this violence, and the ongoing impact of cultures of shame and stigma in preventing disclosure and bystander intervention. This work highlights the need to expand the scope of contemporary research and policy responses to sexual violence in Bangladesh. Highlights: Examines "everyday" experiences of sexual violence in Bangladesh, using innovative online methods. Participants experienced sexual violence across diverse spatial and relationship contexts. Findings highlight the centrality of class in shaping experiences and contexts of sexual violence. Responses of bystanders and disclosure recipients was typically poor, and suggests a need for widespread educational efforts.